Hodgkin Lymphoma at the Paediatric Oncology Unit of Gabriel Touré Teaching Hospital, Bamako, Mali: 5-Year Experience - B. Togo; F. Traoré; A. P. Togo; C. B. Traoré; K. Dumke; M. Diawara; A. A. Diakité; M. Sylla; F. Traoré-Dicko; B. Traoré; T. Sidibé (Advances in Hematology)
Introduction. The aim of this retrospective, unicentric study over 5 years is to describe the epidemiologic, pathologic, clinic and therapeutic aspects of children treated for Hodgkin lymphoma in our paediatric oncology unit. Patients and Methods. From January 2005 to December 2009, all children under 18 years of age, with Hodgkin lymphoma were included in this study. The treatment protocol was the GFAOP (Groupe Franco—Africain d'Oncologie Pédiatrique) Hodgkin lymphoma treatment protocol. Results. During the study period, 217 cancer cases were diagnosed in our centre. Of these cases, 7 were Hodgkin Lymphoma (LH) (0.04%). The mean age was 11.7 years. The sex-ratio was 6/1. 4% (5/7) of patients were stage IIB and 28.6% (2/7) stage IIIB of Ann-Arbor classification. There were 3 cases (42.8%) of sclero-nodular subtype, 2 cases (28.6%) of lymphocyte-rich classical HL subtype, 1 case (14.3%) of mixed cellularity and 1 case (14.3%) of lymphocyte depleted subtype. With a median followup of 37 months, 5 patients (71.4%) are alive, and 2 patients (28.6%) died. Conclusion. Broader multicentric studies are needed for more accurate data on this malignancy.